Employment Generation of Small-Scale Enterpise and Poverty Alleviation in Rivers State - Amadi, Chukuemeka Robert; Nwankwo, Nneka Uchenna; Nwikina, Christian Gbarawae; Stella U, Abraham (International Journal of Contemporary Sciences (IJCS), 2024)
Job creation opportunities of small-scale businesses in Nigeria for low-skilled workers should be the key to employment creation, which in turn leads to poverty reduction. The seeks to investigate the effects of the employment generation of small-scale enterprises and poverty alleviation in Rivers State. The study used descriptive statistics and the Z-test for the analyses of the data. The finding revealed that the employment generation of small-scale enterprises has a positive and significant effect on poverty alleviation in Nigeria. In addition, it was established that the economic benefits of participants in small-scale enterprises have a positive and significant effect on poverty alleviation in Nigeria. It is concluded that the employment generation of small-scale enterprises considerably enhanced poverty alleviation in Rivers State. The study recommends that policymakers and governments and their agencies provide the technical, technological, financial, managerial assistance, and infrastructure needed for the optimal use of the enormous employment creation opportunities in the small-scale businesses in Rivers State and Nigeria at large.